(untitled) (Journal of Engineering, 2010)
An experimental and numerical study has been carried out to investigate the heat transfer by natural convection in air-filled annulus between two horizontal isothermal concentric cylinders with and without annular fins under steady state conditions; the inner cylinder surface is maintained at a higher temperature and the outer cylinder surface at a lower one. In the experimental study, the annulus inner surface is maintained at high temperature by applying uniform heat flux to the inner cylinder while the annulus outer surface is subjected to ambient temperature and maintained at low temperature. The experiments were curried out at a range of Rayleigh number (1.81×103 – 4.03×104) for case without fins and (1.08×103 – 2.94×104) for case with fins, at different diameter ratios (η = 2.0, 2.6 and 3.0). The results showed that: (1) increasing the diameter ratio(η) strongly increases the heat transfer rate, (2) increasing Rayleigh number increases the heat transfer rate for any η and (3) attaching annular fins to the inner cylinder surface of (No. of fins/cm) of 1.25 and (fin height/gap width) of 0.143, 0.186 and 0.286 reduced the mean Nusselt number ( Nu) within (16.3 - 29.7) percent of that for the case without fins at the same Rayleigh number. In the numerical study, only the case without fins was investigated. The buoyancy driven fluid flow resulting from the temperature difference between the cylinders, is assumed to be steady, laminar, two dimensional and symmetric about the vertical center-line. Only half of the domain needs to be modeled from symmetry considerations. Navier-Stokes and energy equations are expressed in vorticity-stream function form and discretized via finite difference method. The Rayleigh number (based on gap width) varied from l02 to l05 with the influence of diameter ratio obtained near a Rayleigh number of 104. Results for the local and mean Nusselt number, the contour maps of the streamlines and isotherms are presented, to show some of the flow and heat transfer characteristics. The results numerically obtained showed a good agreement with the present experimental data.